The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/agronomy10010132
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Organic and Inorganic Nitrogen Fertilizers Affects Soil Prokaryotic Communities Compositions

Abstract: As a fundamental part of the soil ecosystem, prokaryotes are involved in the preservation of soil functions. However, little is known of how the combined application of long-term organic and inorganic nitrogen fertilizer affects the prokaryotic communities’ dynamics at a paddy field. A long-term positioning experiment initiated in 2013 with four treatments (NO: no N fertilizer, CN: 100% urea N with no organic fertilizer, PM: 80% urea N plus 20% N with pig manure, CM: 80% urea N plus 20% N with compost) were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…+ first before being absorbed by the plants, then the plants release the H + ions into soil, which thereby decreases soil pH [99], whereas the ability of organic compost to decrease soil pH may be attributed to the formation of organic acids during the continuous decomposition of organic compost after being incorporated into soil. However, the efficiency of organic composts for decreasing soil pH depends on the type of organic manure.…”
Section: Comprehensive Evaluation Of the Relationship Between Inm Strmentioning
confidence: 99%
“…+ first before being absorbed by the plants, then the plants release the H + ions into soil, which thereby decreases soil pH [99], whereas the ability of organic compost to decrease soil pH may be attributed to the formation of organic acids during the continuous decomposition of organic compost after being incorporated into soil. However, the efficiency of organic composts for decreasing soil pH depends on the type of organic manure.…”
Section: Comprehensive Evaluation Of the Relationship Between Inm Strmentioning
confidence: 99%
“…Soybean planting and covering had a significant effect on the richness of soil microbiomes, as measured by both the ACE index and the Chao1 index [ 22 ]. The results showed that soybean planting and covering (ASB, USB, and WSB treatments) significantly increased the microbial richness than the control (CK), more so in the fungal community than in the bacterial community ( Table 3 , S5 Table in S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…OTUs were classified according to the SILVA ribosomal RNA gene database for bacterial and archaeal species [ 20 ] and to the UNITE database for the molecular identification of fungi [ 21 ]. The richness of soil microbiomes were measured by both the ACE (abundance-based coverage estimator) index and the Chao1 index (number of expected OTUs in a sample among all OTUs identified in all samples) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen fixation by mycorrhizal fungi is essential for sustainable cultivation to be productive [62][63][64]: for this, it is essential to know certain edaphic parameters, since within the Fabaceae family, there are species indifferent edaphic to pH, being able to be acidophilic exclusively or basophilic. Jakubus and Graczyk [65] studied the variability of edaphic microelements in fields with Lupinus albus L., oscillating the soil pH between 6.5-7.0, soils in which some of the associations that we study growth (TP, TT, PA and LR): favoring this type of cover crop, it would not be necessary to carry out organic and inorganic fertilizations [66].…”
Section: Discussionmentioning
confidence: 99%